2015
DOI: 10.1186/s40623-015-0249-4
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the solar wind conditions during an extreme geomagnetic storm: a case study of the event that occurred on March 13–14, 1989

Abstract: The solar wind conditions of an extreme geomagnetic storm were examined using magnetic field observations obtained from geosynchronous satellites and the disturbance storm-time (Dst) index. During geosynchronous magnetopause crossings (GMCs), magnetic field variations at the magnetosheath, which is the modulated interplanetary magnetic field (IMF), were observed by geosynchronous satellite. The dawn to dusk solar wind electric field (VB S ) was estimated from the Dst index by using an empirical formula for Dst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 30 publications
(32 reference statements)
1
27
0
Order By: Relevance
“…This event has been used as a historical benchmark from a scientific perspective (Wei et al, ) as well as a reference event for power grid reliability legislation (North American Electric Reliability Corporation, ). However, solar wind measurements were sparse (Nagatsuma et al, ) and the spatial coverage provided by ground‐based magnetometers was far below current levels. (Ngwira et al, ) As noted above, global simulations are difficult without solar wind observations, and the fidelity of modeling GIC strongly depends on the distance from available magnetometer data to the power grid infrastructure (Butala et al, ).…”
Section: Benchmarking and Forecastingmentioning
confidence: 99%
“…This event has been used as a historical benchmark from a scientific perspective (Wei et al, ) as well as a reference event for power grid reliability legislation (North American Electric Reliability Corporation, ). However, solar wind measurements were sparse (Nagatsuma et al, ) and the spatial coverage provided by ground‐based magnetometers was far below current levels. (Ngwira et al, ) As noted above, global simulations are difficult without solar wind observations, and the fidelity of modeling GIC strongly depends on the distance from available magnetometer data to the power grid infrastructure (Butala et al, ).…”
Section: Benchmarking and Forecastingmentioning
confidence: 99%
“…(a) The VBs obtained from the Dst index, represented by the thick black line, and VBs obtained from GOES 06 and 07 observations with the estimated solar wind speed during 13 and 14 March (Nagatsuma et al, ). (b) The H GUAM‐LNP (difference between the H horizontal component at equator GUAM and nonequator station LNP).…”
Section: Observation and Analysismentioning
confidence: 99%
“…The solar wind parameters were not very extreme at the time of the 1989 storm. For example, Nagatsuma et al (2015) estimated that the solar wind speed of 960 km/s and southward interplanetary magnetic field Bz of −50 nT continuing for 5 h drove the main phase of the March 1989 storm, whereas Lakhina and Tsurutani (2016) indicated that the interplanetary driver of the March 1989 storm included multiple shocks, multiple sheaths, and multiple magnetic clouds. It is therefore reasonable to assume that a perfect "slot machine"-type combination of solar wind parameters sometimes results from the complex interactions of chains of coronal mass ejections during their propagation in the solar wind (Cid et al 2014;Kataoka et al 2015).…”
Section: Rc-type Slow Gicsmentioning
confidence: 99%